2015
DOI: 10.1007/s12262-015-1410-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Outcome and Complications in Laparoscopic Hernia Repair of Inguinal Hernia With Mesh Fixation Using Fibrin Glue vs Tacker

Abstract: Although laparoscopic repair offers a quick and less morbid way of treating hernias, complications like hematoma, seroma, neuralgia, recurrence, mesh infection, hydrocele, etc. are known. The present study was undertaken to compare various clinical outcomes between mesh fixation using fibrin glue and mesh fixation with tacker in a 3-months follow-up. One hundred patients aged 18 to 60 years having inguinal hernia admitted in Poona Hospital and Research Centre, Pune, between October 2012 and November 2014 for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…10 However, in few studies the incidence of postoperative urinary retention was significantly more in the tacker group when compared to the fibrin glue group and the incidence correlated with the number of tackers used. 12,13 Even though mesh hernioplasty has drastically reduced the recurrence rates of hernia, it is associated with the morbidity of chronic postoperative pain which can severely impair the quality of life. 14 A variety of etiologies have been proposed for the cause of chronic pain following hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, in few studies the incidence of postoperative urinary retention was significantly more in the tacker group when compared to the fibrin glue group and the incidence correlated with the number of tackers used. 12,13 Even though mesh hernioplasty has drastically reduced the recurrence rates of hernia, it is associated with the morbidity of chronic postoperative pain which can severely impair the quality of life. 14 A variety of etiologies have been proposed for the cause of chronic pain following hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…Shinde et al [17] and Ceccarelli et al [18] reported an average hospital stay of 1 day, while Chandra et al [19] reported an average hospital stay of 2.26 days. All of the patients in our study were discharged on the postoperative first day.…”
Section: Discussionmentioning
confidence: 99%
“…These studies typically mention that FS is preferable to tissue-penetrating fixation as it is likely to prevent chronic pain. However, studies lack adequate followup to investigate this claim [8,[17][18][19]. By not including chronic pain in our cost analysis, we miss a substantial cost difference between the two alternatives that would undoubtedly favor FS.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events of laparoscopic inguinal hernia repair include neuralgia and seroma [6][7][8][9]. An area of interest is the choice of fixation device used in securing a prosthetic mesh over the compensated tissue in the abdominal wall.…”
Section: Introductionmentioning
confidence: 99%